ダイ49ジ ナンキョク チイキ カンソクタイ ナツタイ ニオケル コショウ カンソク - 工藤, 栄; クドウ, サカエ; 田邊, 優貴子; タナベ, ユキコ; 飯田, 高大; イイダ, タカヒロ; 辻本, 惠; ツジモト, メグム; 小川, 麻里; オガワ, マリ; 伊村, 智; イムラ, サトシ; et al. (情報・システム研究機構国立極地研究所, 2008)
P(論文) 第49次日本南極地域観測隊(第49次)夏隊において,湖沼観測として湖沼環境観測,生物・生態学的研究試料としての湖水と湖底の生物群集採取,及び現場実験を宗谷海岸露岩域にある複数の湖沼で実施した.この湖沼観測報告は南極観測事業第VII期計画の一般プロジェクト研究(P3)「極域環境変動と生態系変動に関する研究」及びモニタリング研究観測(M4)「生態系変動のモニタリング」の両課題にかかわる観測を記録したものである.野外観測は2007年12月22日から2008年2月13日の期間,砕氷船「しらせ」が昭和基地沖近傍に滞在中に実施した.今回は夏季の湖沼環境変動と湖底の生物(藻類群集)の応答を集中的に観測すべく,スカルブスネスの長池にて観測とサンプリング・現場実験を繰り返し実施する一方,きざはし浜生物観測小屋から徒歩日帰り圏内にある周辺の14湖沼,及びヘリコプターを利用した日帰り観測にてスカルブスネス東部の4湖沼,及び他の露岩,スカーレンにあるスカーレン大池,ラングホブデ域の雪鳥池・東雪鳥池,ぬるめ池にて湖沼水質環境観測と試料採集を適宜実施した.このうち,スカルブスネス東部のなまず池 (仮称)では潜水による水中設置ビデオ装置の回収と,湖底のコケ類・藻類が作り上げている「とさか・筍状」の群落の採集,ラングホブデぬるめ池では湖底から小型カイアシ類の定量サンプリングを実施,これらを研究試料として日本に持ち帰ることができた.また,第47次隊により雪の堤防の決壊の発見(第46次越冬期間中に決壊したとみられる)が報告されたラングホブデ南部の平頭氷河末端にあった「氷河池」(仮称)の現状視察も実施,決壊前後での3m以上と思われる大幅な水位変動痕からフィルム状の生物試料を採集し持ち帰った. Observations on the limnological properties, samplings of waters and bottom assemblages for biological and ecological studies, and some field experimental studies at several lakes in Soya Coast ice-free areas, were carried out during the austral summer season in the 49th Japanese Antarctic Research Expedition (JARE), 2007-2008. These studies were planned as one of the research projects named, "Studies on the changes of polar environments and ecosystems (P-3)" and the monitoring studies named "Monitoring for ecosystems (M-4)" during the 7th term of the Japanese Antarctic Research Expedition Plans. Field studies were done from 22 December 2007 to 13 February 2008, while our Ice Breaker Shirase stayed at/near off Syowa Station. To clarify the relationships among seasonal changes of environmental factors and biological responses, frequent field observations were performed at Naga Ike, one of the freshwater lakes in the Skarvsnes ice-free area. General limnological and biological samplings at the other lakes in the area (14 lakes near the Kizahasi Beach field base camp) were also done during the term. Observations and samplings distant from the base camp, four lakes in eastern Skarvsnes, a lake in Skallen, and three lakes in Langhovde, were also done using a helicopter for ...